The kings and the pawns : collaboration in Byelorussia during World War II - Rein, Leonid (Studies on war and genocide, 2011)
Collaboration in occupied Europe : theoretical overview -- Historical background -- German policies in Byelorussia (1941-1944) -- Byelorussian "state-building" : political collaboration in Byelorussia -- The cross and the hooked cross : the Church's collaboration in occupied Byelorussia -- Collaboration in the politics of repression -- Military-police collaboration in Byelorussia -- Appendix: SS and military ranks -- Glossary